Effects of Advanced Age, Pituitary Pars Intermedia Dysfunction and Insulin Dysregulation on Serum Antioxidant Markers in Horses - Agnieszka Żak; Natalia Siwińska; Elżbieta Chełmecka; Barbara Bażanów; Ewa Romuk; Amanda Adams; Artur Niedźwiedź; Dominika Stygar (Antioxidants, 2020)
The study aims to assess the impact of age, pituitary pars intermedia dysfunction (PPID) and insulin dysregulation (ID) in horses on selected oxidative stress markers. The study includes 32 horses, divided into three groups: “young” adult group (aged 8–16 years old) “geriatric” group (aged 18–24 years old) and the “PPID” group (aged 15–31 years old). The PPID group was further divided into two subgroups: PPID ID+ and PPID ID− based on presence or absence of ID. We measured serum antioxidant stress markers in all horses: total oxidant status (TOS), total antioxidant capacity (TAC), ceruloplasmin (CER), lipofuscin (LPS), malondialdehyde (MDA) and thiols concentrations (containing sulfhydryl group -SH) as well as enzymatic systems: total superoxide dismutase (SOD), cytoplasmic SOD (CuZnSOD), mitochondrial SOD activity (MnSOD). Total serum thiols were significantly lower in the geriatric group and in the PPID group compared to the young group. The MnSOD concentration was higher in the PPID ID+ group compared to the PPID ID−. LPS and MDA concentrations were lower in the PPID ID+ group compared to the PPID ID− group. In the selected study groups of horses, older age, the presence of PPID and ID in the case of PPID had no effect on the studied oxidative stress markers.